“Beyond Kant”: a New Genealogy of Morals by M. Foucault - Baranova, Jūratė (Problemos, 2003)
This article analyses the turn towards morality by French postmodernist and poststructuralist Michel Foucault. It emphasises the question, what is the distance between Foucault and Kant. Foucault can be considered as a radical Antikantian, when one takes into account his attitude toward anthropology. Besides that, the Antikantianism of Foucault stems from the interpretation of relation between power and subject following Nietzschean genealogy. Notwithstanding his Antikantianism Foucault is not so ardent critic of Modernity as Alasdair Maclntyre. In Kant’s attitude toward present elaborated in the article „What is EnĮightenment?“ he finds echo of his own project - „ontology of present“. But Foucault’s investigation of morals goes into opposite direction than Kant’s. Kant looked for a priori and timeless foundations of morals. Foucault in his genealogy investigates historical structures of morality. In every historical culture he discusses the same repeating structural contours of morality. He sees the connection between power games and relation towards oneself (rappon a soí) in Greek, Roman and Christian cultures.